Observational study of survival outcomes of people referred for ‘fast-track’ end-of-life care funding in a district general hospital: too little too late? - James Richards; Jo Morrison; Charlie Davis; Cherry Choudhary; Ryan Beazley (BMJ Open Quality)
Background End-of-life care requires support for people to die where they feel safe and well-cared for. End-of-life care may require funding to support dying outside of hospital. In England, funding is procured through Continuing Healthcare Fast-Track funding, requiring assessment to determine eligibility. Anecdotal evidence suggested that Fast-Track funding applications were deferred where clinicians thought this inappropriate due to limited life-expectancy.Aim To evaluate overall survival after Fast-Track funding application.Design Prospective evaluation of Fast-Track funding application outcomes and survival.Setting/participants All people in 2021 who had a Fast-Track funding application from a medium-sized district general hospital in Southwest England.Results 439 people were referred for Fast-Track funding with a median age of 80 years (range 31–100 years). 413/439 (94.1%) died during follow-up, with a median survival of 15 days (range 0–436 days). Median survival for people with Fast-Track funding approved or deferred was 18 days and 25 days, respectively (p=0.0013). 129 people (29.4%) died before discharge (median survival 4 days) and only 7.5% were still alive 90 days after referral for Fast-Track funding.Conclusions Fast-Track funding applications were deferred for those with very limited life-expectancy, with minimal clinical difference in survival (7 days) compared with those who had applications approved. This is likely to delay discharge to the preferred place of death and reduce quality of end-of-life care. A blanket acceptance of Fast-Track funding applications, with review for those still alive after 60 days, may improve end-of-life care and be more efficient for the healthcare system.